Characterisation of Bauxite and Laterite ores in Yercaud Hill, Salem District, Tamil Nadu, India - Aravindan.S; Balabantaray, Sanjay Kumar; Bharathiraja. S (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
The charnockitic suite of rocks underlying the bauxite deposits of Yercaud Hill consists of quartz, plagioclase and potash feldspar, ortho and clino-pyroxenes, garnet and secondary hornblende. Bauxite consists mainly of aluminum hydroxide minerals. Bauxite occurs in Yercaud Hill as a part of the Eastern Ghats range of Tamil Nadu of the Achaean age. It is formed due to residual weathering and lateritization of Achaean charnockite. In the study area, bauxite consists of hydrous aluminum oxides, aluminum hydroxides and laterites, which are mostly found in humid tropical climatic conditions due to intense weathering of the parent rock. The XRD study shows that gibbsite (Al (OH)3), goethite (FeO(OH)) and hematite (Fe2O3) are the major minerals in the bauxites. From the XRF analysis, the major oxides are Al2O3, Fe2O3, SiO2, TiO2, P2O5, and Cr2O3. Based on the Al2O3, SiO2, Fe2O3 ternary plot, bauxites of this region have undergone strong lateritization. According to the chemical classification of laterites, Yercaud bauxites are categorized as Ferrite and Bauxitic Ferrite with some amounts of bauxite. At high Al2O3 weight percentage (86%), low Fe2O3 concentration (10.56%), and TiO2 (0.49%) indicates it as a high-grade Bauxite of aluminium hydroxides mineral Gibbsite (Exploited mines-III, Semmedu). High Fe2O3 constitutes (77.61% by weight), low Al2O3 (18.22%) and 0.89 % TiO2 portrays it as iron-rich laterite (Exploited mines – I, Manjakuttai). This geochemistry reveals the site-specific Al2O3 weight percentage of bauxite ore within the study area of Shevaroy Hill in Salem district.